Zero-sum subsets of decomposable sets in Abelian groups - Banakh, T.; Ravsky, A. (Algebra and Discrete Mathematics, 2020)
A subset D of an abelian group is decomposable if ∅ ≠ D ⊂ D + D. In the paper we give partial answers to an open problem asking whether every finite decomposable subset D of an abelian group contains a non-empty subset Z ⊂ D with ∑Z = 0.